Comparison of surface defects in Protaper Next and Hyflex EDM files after single clinical use – A stereoscopic evaluation - Faizan Javed; Momina Anis Motiwala; Khan, Muhammad Farhan Raza; Robia Ghafoor (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the surface defects created on the ProTaper Next files versus Hyflex EDM files after single clinical use in molars. Methods: One hundred and fourteen Nickel-Titanium files belonging to two contemporary systems, HyFlex EDM and ProTaper Next, were used to perform complete root canal treatment of a molar tooth. The files were first visually examined and then analyzed under 25.6x magnification using a stereomicroscope for evaluation of surface defects. A photographic record was maintained and studied. Descriptive statistics were calculated for frequency of defects. Chi-square test was used to check the association between file and defect type. Odd’s ratio was calculated to check the strength of association between file type and microscopic presence of defects. Results: Frequency of files showing defects was 14.9%. Deformation of the cutting edge was the most frequently seen defect type, found in 7.9% files. The frequency of fractured files was 3.5%. The odds of microscopic defects in HyFlex EDM is 2.64 times that of ProTaper Next. Conclusion: Even after single clinical use, HyFlex EDM files are more likely to get microscopic defects on their surface compared to ProTaper files. Continuous...